Nota sobre variabilidad en el crecimiento de raices de algodon en estado de plan. - Leidi, E.O.=700 1 Gutierrez, J.C.
(Es, En)
ilus., 21 ref.
Keywords: GOáYPIUM HIRSUTUM; RAICES; SELECCION; SEQUIA; FITOMEJORAMIENTO; ESPAÑA